Networks in healthcare : managing complex relationships - Malby, Rebecca; Anderson-Wallace, Murray (Emerald Group Publishing Limited, 2016)
The growing number of networks delivering healthcare, and professionals learning together to improve care, has created a need for new kinds of management and leadership. This timely book highlights key lessons for network leaders in a world where care must increasingly be managed through partnerships and networks as a response to complex health needs requiring better solutions across health economies. Using their own research and case studies, the authors set out the context: why networks are here to stay; the benefits: why networks work well and for what; the difference between networks and hierarchies and when to use each form to improve care and learn; the different types of network; and how to lead a network effectively. Written for health and social care professionals wanting to set up or currently leading a network, this book by two leading experts is practical, informative, but theoretically grounded. Also useful for academics teaching health care leadership, it includes practical diagnostic materials and up to date examples from care sectors world-wide.